ІЗ ДОСВІДУ ВПРОВАДЖЕННЯ ЗМІШАНОГО НАВЧАННЯ ПРИ ВИВЧЕННІ АНГЛІЙСЬКОЇ МОВИ ЗА ПРОФЕСІЙНИМ СПРЯМУВАННЯМ (World Science, 2020)
The article deals with the issue of blended learning adoption into teaching the second (master’s degree) level in the field of expertize 281 ‘Public Administration’ seekers English for Specific Purposes.The foreign professional language new methodology introduction aims to solve the problem of qualitative compensation of learning content by the retrainees: the Civil Protection and Fire Safety professionals, air- communicators and firefighting radiotelephone operators as the result of a high level of classes missing caused by occupational necessity.